Financialization and housing: Between globalization and Varieties of Capitalism. (April 2016) - Fernandez, Rodrigo; Aalbers, Manuel B
In the literature, one finds various explanations for the rise of financialized capitalism. In the different strands of financialization literature, housing either plays a minor role or is simply seen as one of the bearers of financialization. The relations between housing and financialization are under-researched and under-theorized. This article, first, looks at the rise of housing finance as an integral part of macro-economic policy, and second, at the role of financial globalization in the rise of housing finance. Housing is seen as an absorber of a 'wall of money', but the absorption of finance by housing is a very uneven process. Four trajectories of national institutional structures are suggested, and it is discussed how capital flows are absorbed in each of these trajectories. Finally, it is discussed what this tells about the geographies of financialized capitalism, and its relations to debt, housing, mortgage markets and the spatial fix.